Arctic Risk in Urban Spaces (ARUS) : Report of meeting 16th & 17th January 2018 - Chapman, David; Larsson, Agneta (Luleå tekniska universitet, Arkitektur och vatten, 2018)
Report from the ARUS workshop in Abisko Research Station of the 16th and 17th January 2018. The workshop was used to develop a project agenda and key issues around changing risks in the Arctic public realm. Whilst this workshop was exploratory, the aim was to identify design challenges to urban space that climate change could bring for soft mobility. The objective was to develop a research strategy that can develop ways to adapt Arctic settlements to these new environmental risks. The goal is to grow these agendas into research applications and funded research.